Tarumã Mirim Park Hotel: Arquitetura regional aplicada à prestação de serviços turísticos na Amazônia - Siqueira, Bruna Araújo de (Brasil, 2022)
With the challenge of developing the End of Course Work in Architecture at the Federal University of Amazonas, the purpose of this is entangled by the investigation of the Amazonian floating architecture and propose better uses for adequacy in tourism little experienced by the Amazonian citizen. Firstly, through the experience of living in one of the Brazilian capitals most isolated from the rest of Brazil, a reflection about local tourism is initiated, which is complemented by on-site visits, analysis by geoprocessing technology programs and interviews with civilians. The result found is the simplicity of the bioclimatic perception of the natural factors of sun, rain and wind translated into architecture.Therefore, the floating architecture was found to be a viable alternative to work with bioclimatic solutions that are favorable to the Amazon region.